FACTORS RELATED TO DEVELOPMENT OF SIDE EFFECTS IN HEMODIALYSIS PATIENTS AT DR. ADJIDARMO LEBAK HOSPITAL IN 2023 - Suryana, Irma; Fauzi, Achmad (HEARTY, 2024)
Background: Chronic kidney failure is a kidney disorder characterized by abnormalities in kidney structure and function, patients with kidney failure are characterized by a decrease in glomerular filtration rate so that they require kidney function replacement therapy, such as Hemodialysis. This Hemodialysis therapy plays an important role in ensuring patient survival in addition to physical side effects, there are also often psychological side effects such as anxiety, quality of life and depression that can be felt by patients undergoing Hemodialysis therapy. Research Objective: Knowing the factors associated with the development of side effects in Hemodialysis patients at dr. Adjidarmo Lebak Hospital in 2023. Research Methodology: Descriptive with research design using cross sectional approach. Research Findings: Obtained from 85 respondents, half of the respondents 50,6% are older which is more than the same as 45 years with most respondents 65,9% being female and almost half of respondents 37,6% having an average high school education. The results also found that most respondents 56,5% with worker status. Most respondents 75,3% had comorbidities. And as much as 35,3% of hemodialysis is 7-12 months old. 34,1% of hemodialysis has been > 12 months, and 30,6% have been hemodialysis for 1-6 months. The results also showed the results of the relationship between the variables of education level and the variable duration of hemodialysis with the development of side effects in Hemodialysis patients, as well as the absence of the relationship of variables age, gender, occupation and comorbidities to the development of side effects in Hemodialysis patients. Conclusion and Recommendations: The results of this study are expected to be used as a basis for awareness of high incidence of anxiety, especially in patients who have just undergone hemodialysis. In addition, the results of this study can also be the basis for future researchers to develop management interventions to overcome anxiety in patients who have just undergone hemodialysis.